Performance evaluation and calibration of capacitance sensor for estimating the salinity of reclaimed land - Kim, Donggeun; Son, Younghwan; Park, Jaesung; Kim, Taejin; Jeon, Jihun (International Journal of Agricultural and Biological Engineering, 2020)
Generally, soil moisture and salinity in reclaimed land are monitored using soil dielectric sensors such as time domain reflectometry, frequency domain reflectometry, and capacitance. The soil dielectric sensor measures apparent dielectric permittivity. However, apparent dielectric permittivity is affected by soil moisture, salinity, and texture. In this study, performance evaluation and calibration of a dielectric sensor (5TE; METER Group, Inc., Pullman, WA, USA) for monitoring soil salinity were performed. Laboratory calibration tests were completed, incorporating various levels of dry density, water content, and salinity. The soil salinity was determined by the electrical conductivity (EC)1:5 method. The volumetric water content as measured by the sensor was affected by dry density and water content. Generally, it linearly increased as dry density and water content increased. However, when dry density or water content was high, the measured value of the sensor increased nonlinearly. The bulk EC measured by sensor had no specific correlation with EC1:5. The EC1:5 measurement had a linear relationship with the gradient of θ and θs. Therefore, it can be estimated with a simple linear equation using θ from the soil test and θs from the capacitance sensor. The R2 value of the EC1:5 estimation equation was 0.98. The proposed equation requires θ from the gravimetric sample and θs from the sensor. Therefore, in the case of monitoring salinity using a sensor, it is recommended to measure the water content with a tensiometer.Keywords: salinity, capacitance sensor, volumetric water content, reclaimed land soil, saline soilDOI: 10.25165/j.ijabe.20201301.3905Citation: Kim D, Son Y, Park J, Kim T, Jeon J. Performance evaluation and calibration of capacitance sensor for estimating the salinity of reclaimed land. Int J Agric & Biol Eng, 2020; 13(1): 206–210.